Pattern and Management of Obstructive Jaundice in Wad Medani Teaching Hospital, March 2014 -2015 - HR Adam, Rahamtalla; Elshiekh, Ahmed A.; Mohammed, Mustafa I (Gezira Journal of Health Sciences, 2016)
Abstract:                                                     Obstructive jaundice is not uncommon in this area certainly with what is reported in the literature, malignant jaundice is more common than choledocholithiasis. The pre-operative management followed the international guidelines; most of the surgery done to the malignant jaundice was palliative because of the late presentation. Endoscopic service in management of obstructive jaundice is important and shall be utelized after completion of the new GIT Centre-Wad Medani Hospital. This study was a prospective cross sectional descriptive study, conducted in Wad Medani hospital - Gezira state – Sudan from March 2014 to March 2015. Wad Medani Teaching Hospital is a tertiary hospital with 600 beds serving all Gezira state and nearby states  Material and Method: 124 patients admitted to hospital with symptoms and signs of obstructive jaundice including; yellow coloration of the sclera, dark urine,pale stools, itching, with or without the association of vomiting, abdominal pain, abdominal mass and weight loss. Diagnosis was confirmed by history, examination and biochemical and radiological investigations.The data was analyzed by computer using SSPS. Results: 52(41.9%) were males and72 (51.8%) were females, with male to female ratio of 1:1.3. The cases of obstructive jaundice were found to be distributed among their age groups from 18-40yr (15.3%),41-60yr(31.5%) , 60yr and above (53.2%). Definitive diagnosis after completion of investigations results showed that cases due to common bile duct (CBD) stone and carcinoma of the head of pancrease were 55 (44.4%) and 52 (41.9%) respectively. The relation between the diagnosis and sex results showed CBD stone in females was 37(51.4%) where as in males  carcinoma of the head of pancrease was 25(48.11%), ERCP was used in 67(54%) patients both for diagnostic and therapeutic indications. The operative intervention was also studied for all patients with obstructive jaundice and the results showed that 48(38.7%) patients underwent surgical intervention with 7(5.6%) CBD exploration and 41(33.1%) by pass surgical operation. Conclusion: ERCP has a promising role in the study area in managing patients with obstructive jaundice. The family physicians   have an important role to play in early detection and referral of patients with obstructive jaundice to hospitals to avoid delayed presentation and minimize the harmful effects of hyper bilirubinemia on the   liver so the step should start with how to detect the case and after that what to do for the case before referral to nearby hospital.